Vai trò trung gian của năng lực kết nối trong mối quan hệ giữa mục tiêu đa dạng hóa và kết quả hoạt động của công ty: Nghiên cứu thực nghiệm tại Thành phố Hồ Chí Minh - Phan Như , Minh; Lã Anh , Đức; Trần Hà Minh , Quân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This study investigates the impact of differentiation goals on performance growth. Furthermore, this study investigates the mediating role of networking capability in the above relationship. Based on a data set of 285 managers in Ho Chi Minh City, this study found that networking capability mediated the relationship between differentiation goals and performance growth. These results contributed to the literature on resource-based view theory by introducing a strategic capability for Vietnamese firms, networking capability. Then, the result implies some practical contributions for firms in Ho Chi Minh City to build networking capability, leading to enhance performance growth.